Pengembangan Aplikasi Perangkat Bergerak Sistem Informasi Cagar Budaya Malang Raya dengan Fitur Tampilan Virtual Reality dan Lokasi Terdekat - Muhammad Budi Fauzan; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Cultural heritage is an area where the preservation of people's lives and their lives are protected by law from the danger of extinction (Kemendikbud, 2016). Malang Raya is one of the oldest cities in East Java, Malang Raya has existed since the Kanjuruhan Kingdom, because of this, Malang Raya has many historical buildings, some of which are included in the category of cultural heritage. However, due to the emergence of the Covid 19 pandemic in 2020, this has resulted in the closure of public access to visit cultural heritages in Malang Raya. Based on these problems, in this study an Android-based application will be developed, which can display these cultural heritage environments in the form of Virtual Reality (VR). With this application, people who cannot visit the cultural heritage will be able to feel the same thing as visiting the place in person. There are two types of testing on this application, namely Black Box testing and usability testing. Black Box testing is used to ensure that the functionality of the application can run properly and correctly. While usability testing is used to find out the level of ease of use of this application later. In Black Box testing, it was found that all test cases were valid. Meanwhile, for usability testing, the System Usability Testing (SUS) average score was 82 points. It can be concluded that this application is easy to use by users.